1991
DOI: 10.1016/0304-3959(91)90092-c
|View full text |Cite
|
Sign up to set email alerts
|

Increased postoperative pain and consumption of analgesics following acupuncture

Abstract: Acupuncture was given to patients before (preoperative-acupuncture group, PRE-ACU, n = 25) or after (postoperative-acupuncture group, POST-ACU, n = 25) operative removal of impacted mandibular third molars. Sixty patients did not receive acupuncture and participated as a control group (CG). All patients completed a questionnaire in order to characterize state tension and stress, degrees of neuroticism, extroversion, depression and psychosomatic disorders. We also recorded intraoperative discomfort and pain int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 16 publications
1
29
0
2
Order By: Relevance
“…Onlv one stud) fulfilled more than 85% of the required criteria f37). Five studies fuifilJed between 707o and 84% of the ctiletia (39-41, 13 45, 4B), three met 6070 to 69% (38,46,52) and six studies met less than 60y. (42,47, 4q-SI, 5t.IJ"\en out of the l5 .tudip5 \^e.p in favour of acupuncture and 4 demonstrated no effect.…”
Section: Resurasmentioning
confidence: 99%
“…Onlv one stud) fulfilled more than 85% of the required criteria f37). Five studies fuifilJed between 707o and 84% of the ctiletia (39-41, 13 45, 4B), three met 6070 to 69% (38,46,52) and six studies met less than 60y. (42,47, 4q-SI, 5t.IJ"\en out of the l5 .tudip5 \^e.p in favour of acupuncture and 4 demonstrated no effect.…”
Section: Resurasmentioning
confidence: 99%
“…Ekblom et al 20 concluded that acupuncture application before or immediately after surgical removal of impacted mandibular third molars raised pain levels during postoperative period. However, acupuncture treatment was applied either before or after surgical procedure and electrical stimulation was not used in this study.…”
Section: Acupuncture For Postoperative Dental Painmentioning
confidence: 99%
“…In einer spä teren Studie, bei der die Akupunktur be reits intraoperativ durchgeführt wurde, konnte kein analgetischer Effekt beobach tet werden [4]. Ekblom et al [5] beobach teten sogar eine Zunahme von Schmer zen und Analgetikaverbrauch in der Aku punkturgruppe nach Kieferoperationen. Kotani et al [10] konnten dagegen zeigen, dass eine paravertebrale Nadelung bei Pa tienten, die sich abdominellen Eingrif fen unterziehen mussten, den postopera tiven Opiatbedarf um ca.…”
Section: Schlüsselwörterunclassified